Josef Pekař in the Post-velvet World of Czech Historiography - Havelka, Miloš (Dějiny – teorie – kritika, 2006)
What was known as the "Goll School" and especially the most prominent representative of its first generation, Josef Pekař, for many years formed the main current of Czech conservative-Catholic historiography that developed in opposition to the Protestant-progressive concept of Czechoslovakia represented after Palacký above all by T.G. Masaryk. In many respects Marxist historiography drew on this latter school, and so the historical achievements of the Goll School were ideologically rejected and politically excluded. The "Velvet Revolution" opened up the possibility of an objective assessment of the contributions of the Goll School and especially the long banned Josef Pekař. With an eye to the literature that has so far been published on Pekař, this article seeks to show the state of research by offering an analysis of the various different areas of historical study addressed by Goll, and criticises continuing shortcomings in the three Pekař monographs that have hitherto been published. The article looks in particular at questions of Pekař's historical understanding of the concept and interpretation of the Hussite movement, the reconstruction of the concept and message of the unfinished third volume of Pekař's Knihy o Kosti, the interpretation of Pekař's political attitudes during the 1st World War and especially his conception of constitutional issues, his understanding of the nation and the associated questions of Pekař's nationalism, attitude to the Germans and also his demonstrable anti-semitism.